Diseño de una silla de ruedas eléctrica articulada con Posicionamiento Vertical – horizontal para beneficio de las Personas con Discapacidad Física - Vizuete Andrade, Rubén Dario (2016)
The research project deals with the design of an articulated electric wheelchair with vertical - horizontal positioning for the benefit of people with physical disabilities that improve their standard of living, making them in turn more independent; It must be kept in mind that at present the availability of electric wheelchairs in the country is nil, having the same to be imported with exorbitant costs. Due to this problem, the design of an articulated electric wheelchair with vertical - horizontal positioning is the best option to help people with reduced physical capacities, allowing to meet the needs of users. In order to ensure that the prototype has a high quality as imported, all the elements that constitute the wheelchair were designed with existing materials, easy to acquire as well as plates that act as beams, pipes that in turn act as columns, of equal Actuators, motors, batteries, wheels and servomotors were selected. It was determined that the economic benefit of the construction of the articulated electric wheelchair versus an acquired wheelchair is high and with less waiting time to use it, with the same standards and good quality as those imported. For these details it is concluded that the project fulfills the general objective which is to design an articulated electric wheelchair with vertical - horizontal positioning for people with physical disabilities, where it was determined that the design and selected materials are acceptable to possess a safety factor in the system of analyzed structures greater than 1. Finally, the respective operating and maintenance manuals were carried out to guarantee the correct functioning during its useful life.